Serum neutralizing capacity and T-cell response against the omicron BA.1 variant in seropositive children and their parents one year after SARS-CoV-2 infection - Seidel, Alina; Jacobsen, Eva-Maria; Fabricius, Dorit; Class, Magdalena; Zernickel, Maria; Blum, Carmen; Conzelmann, Carina; Weil, Tatjana; Groß, Rüdiger; Bode, Sebastian F. N.; Renk, Hanna; Elling, Roland; et al. (Frontiers in Pediatrics, 2023)
Durability of immune protection against reinfection with SARS-CoV-2 remains enigmatic, especially in the pediatric population and in the context of immune-evading variants of concern. Obviously, this knowledge is required for measures to contain the spread of infection and in selecting rational preventive measures. Here, we investigated the serum neutralization capacity of 36 seropositive adults and 34 children approximately one year after infection with the ancestral Wuhan strain of SARS-CoV-2 by using a pseudovirus neutralization assay. We found that 88.9 % of seropositive adult (32/36) and 94.1% of seropositive children (32/34) convalescents retained the neutralizing activity against the SARS-CoV-2 Wuhan strain (WT). Although, the neutralization effect against Omicron BA.1 (B.1.1.529.1) was significantly lower, 70.6% (24/34) of children and 41.7% (15/36) of adults possessed BA.1 cross-neutralizing antibodies. The spike 1 (S1)-specific T cell recall capacity using an activation-induced marker assay was analyzed in 18 adults and 16 children. All participants had detectable S1-specific CD4 T cells against WT, and 72.2% (13/18) adults and 81,3% (13/16) children had detectable S1 WT-specific CD8 T cells. CD4 cross-reactivity against BA.1 was demonstrated in all investigated adults (18/18), and 66.7% (12/18) adult participants had also detectable specific CD8 BA.1 T cells while we detected BA.1 S1 reactive CD4 and CD8 T cells in 81.3% (13/16) children. Together, our findings demonstrate that infection with the ancestral strain of SARS-CoV-2 in children as well as in adults induces robust serological as well as T cell memory responses that persist over at least 12 months. This suggests persistent immunological memory and partial cross-reactivity against Omicron BA.1.